2015
DOI: 10.5935/1806-6690.20150028
|View full text |Cite
|
Sign up to set email alerts
|

Spatial variability of macronutrients in a crop of conilon coffee in the north of Espírito Santo

Abstract: RESUMO -Os solos do Estado do Espírito Santo apresentam baixa fertilidade natural, que frequentemente limita a produção das lavouras devido às deficiências de alguns elementos. No entanto, os mesmos apresentam alto potencial de produção agrícola quando são sanadas as limitações químicas presentes. Objetivou-se no presente estudo descrever a variabilidade espacial dos macronutrientes cálcio (Ca), magnésio (Mg), fósforo (P) e potássio (K) em uma lavoura de café conilon (Coffea canephora Pierre) localizada na áre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…The most prominent culture period expected to promote allelopathic potential is the lag phase. In this phase, metabolite mobilization begins and the synthesis of proteins and specific metabolites occurs without cell multiplication [16]. Next, the calli entered the exponential phase with a high proliferation rate reaching a 21-fold increase in weight at five weeks.…”
Section: Uniqueness Of Coffee Nec For Allelopathy Studymentioning
confidence: 99%
See 1 more Smart Citation
“…The most prominent culture period expected to promote allelopathic potential is the lag phase. In this phase, metabolite mobilization begins and the synthesis of proteins and specific metabolites occurs without cell multiplication [16]. Next, the calli entered the exponential phase with a high proliferation rate reaching a 21-fold increase in weight at five weeks.…”
Section: Uniqueness Of Coffee Nec For Allelopathy Studymentioning
confidence: 99%
“…The Tb/Cf ratio is an indicator of the rate of target biosynthesis in cells; a smaller value indicates faster conversion from Tb to Cf. The conversion occurs gradually following proliferation and may accumulate steadily throughout the culture period, reaching its maximum level at a certain stage and then declining [16].…”
Section: Possible Allelochemicals In Coffee Necmentioning
confidence: 99%
“…kriging) has also been widely used as a management tool for various crops. Studies on sugarcane (Li et al, 2019) and conilon coffee (Santos et al, 2015) have demonstrated that spatial interpolation via kriging can be used to estimate calcium (Ca) and magnesium (Mg) deficiencies in the soil, and may be a useful tool in the process of meeting crop nutritional requirements. Given the importance of coffee and the lack of studies that examine the relationship between spatial variability in soil attributes and yield, studies involving soil nutritional variables are essential for precision agriculture.…”
Section: Introductionmentioning
confidence: 99%
“…linear model.Carmo et al (2016) andSantos et al (2015) fit the same models to coffee yield and plant nutrients in the soil. Nevertheless, few studies have fit models to the relationship between plant nutrients in the soil saturation extract and coffee yield.…”
mentioning
confidence: 99%